2002
DOI: 10.1089/107632702760240562
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Compatibility of Two Biodegradable Tubular Scaffolds Implanted Adjacent to Skin or Buccal Mucosa in Mice

Abstract: Radiation therapy for cancer in the head and neck region leads to a marked loss of salivary gland parenchyma, resulting in a severe reduction of salivary secretions. Currently, there is no satisfactory treatment for these patients. To address this problem, we are using both tissue engineering and gene transfer principles to develop an orally implantable, artificial fluid-secreting device. In the present study, we examined the tissue compatibility of two biodegradable substrata potentially useful in fabricating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Numerous studies have focused on feasibility of using nanofibers or hydrogel-based scaffolds. [15][16][17][18][19][20][21][22][23][24][25] Although a few studies have translated their findings in vivo, 16,17,23 no study to date has demonstrated that the tissue developed on or within biomaterials contributes to restoration of gland function. To overcome these limitations, we propose use of poly(ethylene glycol) (PEG) hydrogels for salivary gland cell transplantation.…”
mentioning
confidence: 99%
“…Numerous studies have focused on feasibility of using nanofibers or hydrogel-based scaffolds. [15][16][17][18][19][20][21][22][23][24][25] Although a few studies have translated their findings in vivo, 16,17,23 no study to date has demonstrated that the tissue developed on or within biomaterials contributes to restoration of gland function. To overcome these limitations, we propose use of poly(ethylene glycol) (PEG) hydrogels for salivary gland cell transplantation.…”
mentioning
confidence: 99%
“…As we previously showed, for in situ testing of a functional artificial salivary gland, a large animal is required, as is an autologous graft cell. 11,16 As shown herein, rhesus parotid glands provide an excellent model for such studies. Each individual animal could provide a cell source via a biopsy of the tail region of the parotid gland with minimal morbidity.…”
mentioning
confidence: 83%
“…[13][14][15] A significant hurdle in developing this device is the choice of an appropriate model for testing a prototype in vivo, because conventional rodent models are too small for effective testing of the in situ placement and function of an artificial salivary gland. 16 In the present study, we used a non-human primate tissue, parotid glands from rhesus monkeys, as a cell source. Rhesus monkeys provide a sizable animal suitable for eventual in vivo testing of a prototype device.…”
Section: Introduction Tmentioning
confidence: 99%
“…No significant changes in clinical chemistry and hematology were seen due to the implantation of tubular scaffolds. [153]. It was reported that, after the PLLA segments were swallowed in vivo by phagocytes, cell damage and cell death were obvious.…”
Section: Polyglycolide (Pga) Polylactide (Pla) and Poly(lactic-co-glmentioning
confidence: 99%